An advanced hybrid supercapacitor constructed from rugby-ball-like NiCo2Se4 yolk–shell nanostructures. (5th May 2021) - Ameri, Bahareh; Mohammadi Zardkhoshoui, Akbar; Hosseiny Davarani, Saied Saeed
Abstract : A facile strategy is developed to fabricate rugby-ball-like NiCo2 Se4 yolk–shell nanostructures (RB-NCS) as the cathode electrode material for hybrid supercapacitors. Abstract : Electrode materials based on the yolk–shell structure are of considerable importance in the energy-storage field. Herein, rugby-ball-like NiCo2 Se4 yolk–shell nanostructures (RB-NCS) are successfully synthesized and developed as an attractive cathode electrode material for hybrid supercapacitors. Benefiting from the high porosity of the obtained structure and desirable electrical conductivity, the as-designed RB-NCS electrode presents a prominent capacity of 258.1 mA h g −1 at 1 A g −1 and an impressive longevity of 92.2% over 14 000 cycles at 20 A g −1 ; meanwhile, a high coulombic efficiency of ≈98.1% is achieved. Considering the achieved excellent results, a hybrid supercapacitor was fabricated with the RB-NCS and AC (activated carbon) materials as the cathode and anode electrodes, respectively, in KOH electrolyte (6 M). The as-fabricated apparatus (RB-NCS(+)||AC(−)) delivered a desirable capacity of 71 mA h g −1 at 1 A g −1 with a good capacity retention of 68.9%. Also, the RB-NCS(+)||AC(−) apparatus reflected maximum energy and power densities of 56.9 W h kg −1 and 812.6 W kg −1 at 1 A g −1, respectively.